Anion exchange resin based on tertiary amine type nitrogen-containing polysaccharide derivative and preparation method of anion exchange resin

By cross-linking and pore-making methods in the emulsion template, a tertiary amine-type polysaccharide-based anion exchange resin with a porous double network structure was prepared, which solved the problems of high resource consumption and difficulty in degradation of traditional ion exchange resins, and realized efficient and environmentally friendly ion exchange resins. exchange effect.

CN119331266AActive Publication Date: 2025-01-21DALIAN UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411583573.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-21
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

Existing ion exchange resins mainly rely on petroleum-based synthetic polymers, resulting in high resource consumption and difficult waste resin to degrade, and cannot be used directly as an environmentally friendly alternative.

Method used

By cross -linked and pores in the emulsion templates by combining water -soluble propeline -containing nitrogen -containing polysaccharides derivatives in the emulsion templates, preparing insoluble polysaccharide derivatives in the emulsion templates at the same time, Forms anion exchange resin with adjustable pores and stable structures.

Benefits of technology

The structural stability and water resistance of the material are realized. The unusamine ratio on the material can be adjusted according to the environment of the environment to achieve a reversible cycle of adsorption and absorbing, and improves the adsorption capacity and environmental friendship.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331266A_ABST
    Figure CN119331266A_ABST
Patent Text Reader

Abstract

The invention discloses anion exchange resin based on tertiary amine type nitrogenous polysaccharide derivatives and a preparation method of the anion exchange resin. The anion exchange resin has the following structural general formula: [A (B) i] n-(CL) j-D, in the formula, [A (B) i] n is a tertiary amine type nitrogen-containing polysaccharide derivative, A is a glycan unit residue, B is a substituent on the glycan unit residue, and the substitution degree is i; d is a compound with polyhydroxy, carboxyl or primary amine; (CL) j is a cross-linking agent with the functionality of j and can be subjected to cross-linking reaction with A and D; the resin disclosed by the invention is an insoluble porous dual-network tertiary amine polysaccharide derivative formed by simultaneously cross-linking a tertiary amine type nitrogen-containing polysaccharide derivative and a compound with polyhydroxy, carboxyl or primary amine, the resin has an adjustable porous morphology and can effectively improve the adsorbability of a material, and a dual-cross-linked network structure can improve the cross-linking density of the material; meanwhile, reversible circulation of adsorption and desorption can be achieved, and high environmental benefits and economic benefits are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fine chemical application, and more specifically, to an anion exchange resin based on a tertiary amine nitrogen-containing polysaccharide derivative and a preparation method thereof. Background Art

[0002] Ion exchange resin is the most mature and widely used ion exchange adsorbent. However, traditional ion exchange resins such as polystyrene resin and polyacrylate resin are petroleum-based synthetic polymers, which consume a lot of fossil resources and waste resins are difficult to degrade and cause secondary pollution. Therefore, it is urgent to develop a renewable and environmentally friendly new material as a substitute for synthetic resin.

[0003] As a renewable resource with abundant reserves in nature, the scientific research and technological development of biomass polysaccharides are of great significance for achieving sustainable development and promoting green transformation. Among cationic adsorbents, tertiary amine nitrogen-containing polysaccharide derivatives show great potential and application value, mainly due to the fact that the tertiary amine group can enable tertiary amine polysaccharides to achieve reversible conversion of hydrophilicity / hydrophobicity and electrical properties, thereby enabling controllable adsorption and desorption. Invention patent ZL201910695375.7 discloses a tertiary amine nitrogen-containing polysaccharide derivative, which utilizes the reaction of monochloro-s-triazine containing a di-tertiary amine group with the hydroxyl group on the polysaccharide unit to efficiently introduce double tertiary amine at one site. It has a good bridging adsorption ability for negatively charged particles, and the hydrophobicity of the s-triazine structure can also promote adsorption. By regulating the degree of group substitution (Carbohydr.Polym.2012,88,132-138.), molecular weight (Langmuir 2024,40,3231-3240.) and hydrophobicity (Environ.Res.2021,201,111489.) of amino polysaccharides, the flocculation adsorption capacity of amino polysaccharide derivatives has been greatly improved. In addition, thermosensitive tertiary amine polysaccharide derivatives (Chem.Eng.J.2021,413,127410.) and tertiary amine-containing amphoteric polysaccharide derivatives (RSC Adv.2018,8,1274-1280.) can be used in more different usage environments. However, the hydrophilic hydroxyl groups and protonated amine groups on the polysaccharides cause the tertiary amine polysaccharides to have poor water resistance. Easily soluble or highly swollen polysaccharide derivatives are obviously not conducive to the multiphase operation of the adsorption process, so they cannot be used directly as ion exchange resins.

[0004] By properly cross-linking tertiary amine polysaccharide derivatives to form a three-dimensional network, insoluble polysaccharide products can be prepared (ZL202210428406.4). Introducing a second cross-linked network into a single cross-linked network can further increase the cross-linking density of the material and reduce the swelling rate (Carbohydr.Polym.2020,242,116320.). On the other hand, the adsorption capacity of ion exchange resins is also affected by the adsorption surface area. The adsorption surface area can be increased by physical pore formation to prepare ion exchange resins with high adsorption capacity.

[0005] However, there are currently no reports on the use of biomass polysaccharide derivatives to prepare porous and swelling-resistant ion exchange resins through a one-step cross-linking method. Therefore, the development of new green and environmentally friendly polysaccharide-based ion exchange resins is of great significance to promoting the high-value utilization of biomass resources and accelerating green transformation. Summary of the invention

[0006] The purpose of the present invention is to overcome the above-mentioned defects of the prior art and provide an anion exchange resin based on a tertiary amine nitrogen-containing polysaccharide derivative and a preparation method thereof, that is, a water-soluble tertiary amine nitrogen-containing polysaccharide derivative and a compound having multiple hydroxyl groups, carboxyl groups or primary amine groups as a second network are simultaneously cross-linked and pore-formed in an emulsion template to obtain an insoluble porous double-network tertiary amine polysaccharide derivative having an adjustable number of weakly alkaline amine groups and hydrophobic groups, and a porous morphology with adjustable pore size, which can greatly increase the adsorption sites. The double cross-linked network structure improves the structural stability and water resistance of the material. At the same time, the electrical properties of the tertiary amine groups on the material can be adjusted according to the environmental pH, and a reversible cycle of adsorption and desorption can be achieved.

[0007] To achieve the above object, the technical solution of the present invention is as follows:

[0008] An anion exchange resin based on a tertiary amine nitrogen-containing polysaccharide derivative, the general structural formula of the anion exchange resin is shown in Formula I:

[0009] [A(B) i ] n -(CL) j -D(Ⅰ)

[0010] In Formula I, [A(B) i ] n It is a tertiary amine type nitrogen-containing polysaccharide derivative, wherein A is a polysaccharide unit residue, B is a substituent on the polysaccharide unit residue, and the degree of substitution is i; D is a compound having multiple hydroxyl groups, carboxyl groups or primary amine groups; (CL) j is a cross-linking agent with a functionality of j, which can undergo cross-linking reaction with both A and D;

[0011] The anion exchange resin is an insoluble porous double-network tertiary amine polysaccharide derivative formed by crosslinking a tertiary amine-type nitrogen-containing polysaccharide derivative and a compound having polyhydroxy, carboxyl or primary amine groups simultaneously.

[0012] Optionally, the pore size of the anion exchange resin based on the tertiary amine-type nitrogen-containing polysaccharide derivative is 0.1 μm to 1.0 μm; the porosity of the anion exchange resin based on the tertiary amine-type nitrogen-containing polysaccharide derivative is 17% to 67%.

[0013] Optionally, in Formula I, the glycan unit residue A includes one or more of starch, cellulose, hemicellulose, chitin, guar gum, chitosan, xylan, glucomannan, cyclodextrin or polysaccharide unit residues prepared by acidolysis, oxidation, crosslinking.

[0014] Optionally, in Formula I, the substituent B on the glycan unit residue has a diamino group with a triazine ring as a bridge group, which can randomly replace the H on -OH or -NH2 at any position on the polysaccharide unit, and the degree of substitution 0 < i ≤ 3. Preferably, the degree of substitution is 0.6 to 0.8. It has the structural general formula shown in Formula I-1:

[0015]

[0016] In Formula I-1, R1, R2, R3, and R4 are each independently selected from -H, C1-C 11 alkyl, C1-C 11 aryl, C1-C8 carboxylic acid, C1-C8 alcohol, C1-C8 thiol or C1-C8 alkoxymethyl. Preferably, R1, R2, R3, and R4 are each independently selected from -H, C1-C3 alkyl, C1-C2 aryl, C1-C4 carboxylic acid, C1-C4 alcohol, C1-C4 thiol or C1-C4 alkoxymethyl.

[0017] Optionally, in Formula I, the compound D having polyhydroxy, carboxyl or primary amine groups is selected from one or more of C1-C8 polyols, C1-C8 polycarboxylic acids, C1-C8 polyamines and polymers containing hydroxyl, carboxyl, primary amine groups.

[0018] Optionally, the polymers containing hydroxyl, carboxyl, primary amine groups include one or more of polyethylenepolyamine, polyvinyl alcohol, polyethylene glycol, polyacrylic acid, carboxymethyl starch and hydroxyethyl cellulose with a molecular weight of 1000 to 67000, preferably a molecular weight of 60000 to 67000; the total number of hydroxyl, carboxyl and primary amine groups on the molecular chain of the compound D having polyhydroxy, carboxyl or primary amine groups ≥ 2.

[0019] Optionally, in Formula I, the tertiary amine-type nitrogen-containing polysaccharide derivative [A(B) i n ​The mass ratio of the compound D having multiple hydroxyl groups, carboxyl groups or primary amine groups is 1:0.02 to 1:0.2. Preferably, the mass ratio is 1:0.08 to 1:0.1.

[0020] Optionally, in Formula I, the crosslinking agent (CL) j It is a compound containing j alkoxymethyl groups with melamine as the bridge group, and the alkoxy groups on it can be randomly replaced by -OH or amine groups containing active hydrogen on A and D, and has the general structural formula shown in Formula I-2:

[0021]

[0022] In Formula I-2, R5 to R 10 are independently selected from -H, -CH2OH, -CH2OCH3, -CH2OCH2CH3, -CH2O(CH2)2CH3 or -CH2O(CH2)3CH3, and R5 to R 10 The total number of -H and -CH2OH is <5.

[0023] Optionally, in Formula I, the tertiary amine type nitrogen-containing polysaccharide derivative [A(B) i ] n With crosslinker (CL) j The mass ratio is 1:0.05 to 1:0.4. Preferably, the mass ratio is 1:0.2 to 1:0.4.

[0024] The present invention also discloses a method for preparing the anion exchange resin based on the tertiary amine nitrogen-containing polysaccharide derivative as described above, comprising the following steps:

[0025] The tertiary amine type nitrogen-containing polysaccharide derivative [A(B) i ] n After adding a compound D having multiple hydroxyl groups, carboxyl groups or primary amine groups into water, adjusting the pH of the solution to 2 to 6 to dissolve it, then adding an oil phase for high-speed emulsification to obtain an emulsion template;

[0026] Adding a crosslinker (CL) to the latex template j After mixing, the mixture is reacted in a closed environment at 20° C. to 60° C. for 0 h to 24 h, and then dried and the oil droplets are washed off to obtain the anion exchange resin based on the tertiary amine nitrogen-containing polysaccharide derivative.

[0027] Optionally, the tertiary amine type nitrogen-containing polysaccharide derivative [A(B) i ] nThe preparation method comprises the following steps: adding a diamino compound containing a monochloro-s-triazine structure and polysaccharide in a molar ratio of 0.1 to 10:1 to 10, wherein the polysaccharide is calculated as polysaccharide unit, to a solvent, stirring and mixing evenly, reacting at 0°C to 200°C for 0.1h to 24h, and after the reaction is completed, precipitating in methanol or deionized water, filtering, washing with anhydrous methanol, drying, and crushing to obtain a tertiary amine type nitrogen-containing polysaccharide derivative [A(B) i ] n .

[0028] Optionally, the solvent includes water, ethanol, isopropanol, butanol, DMF or DMSO.

[0029] Optionally, the tertiary amine type nitrogen-containing polysaccharide derivative [A(B) i ] n The mass ratio of the cellulose to water is 1:1 to 1:20. Preferably, the mass ratio is 1:5 to 1:7.

[0030] Optionally, the oil phase includes one or more of vegetable oil, gasoline, paraffin oil, n-hexane, cyclohexane, toluene, and ethyl acetate.

[0031] Optionally, the volume ratio of the oil phase to water is 1:0.5 to 1:5. Preferably, the volume ratio is 1:3.

[0032] Implementing the embodiments of the present invention will have the following beneficial effects:

[0033] The present invention develops a novel tertiary amine biomass polysaccharide-based anion exchange resin having a porous double cross-linked network structure, wherein the material uses tertiary amine biomass polysaccharide as a matrix and a main component, and the presence of the tertiary amine enables it to adsorb under acidic conditions and desorb in alkaline solutions, thereby enabling the recycling of the ion exchange resin; and the double cross-linked network structure of the present invention has a higher cross-linking density than the single network structure, while the double cross-linked network structure and the hydrophobic triazine group improve the water resistance and stability of the ion exchange resin, making it insoluble in water and having a low swelling rate, and can be conveniently applied to a variety of scenarios; the porous structure can improve the adsorption capacity of the material by increasing the adsorption specific surface area; at the same time, the product is low-toxic or non-toxic, biodegradable, has high environmental and economic benefits, and can be used as a high-efficiency biomass-based ion exchanger. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 a is a flow chart for preparing starch-based ion exchange resin in Example 1, and is also applicable to all examples; Figure 1 b is the reaction equation for preparing starch-based ion exchange resin in Example 1.

[0035] Figure 2a is the infrared spectrum of the starch-based ion exchange resin obtained in Example 1; Figure 2 b is the starch-based ion exchange resin obtained in Example 1 13 C solid state NMR spectrum; Figure 2 c is the thermogravimetric curve of the starch-based ion exchange resin obtained in Example 1.

[0036] Figure 3 a is a scanning electron microscope image of the non-porous starch-based ion exchange resin obtained in Comparative Example 2; Figure 3 b and 3c are scanning electron microscope images and pore size distribution statistics of the porous starch-based ion exchange resin obtained in Example 1; Figure 3 d and 3e are the pore size distribution diagrams of the product obtained in Example 1 measured by high pressure mercury injection.

[0037] Figure 4 a is the effect of the degree of substitution of tertiary amine starch on the elastic modulus and viscosity modulus of the obtained wet product; Figure 4 b is the effect of PVA molecular weight on the elastic modulus of wet product; Figure 4 c is the effect of PVA67000 addition on the elastic modulus of the wet product; Figure 4 d is the effect of the amount of crosslinking agent added on the elastic modulus of the wet product.

[0038] Figure 5 a, b and c are scanning electron micrographs of the porous products obtained when the volume ratio of oil to water in the emulsion is 1:2, 1:3 and 1:4, respectively. DETAILED DESCRIPTION

[0039] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.

[0040] The experimental methods shown in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0041] The tertiary amine type nitrogen-containing starch derivatives 1#, 2# and 3# described in the following examples have the following general structural formula:

[0042]

[0043] The above-mentioned 1#, 2# and 3# tertiary amine type nitrogen-containing starch derivatives are prepared according to the method of patent ZL201910695375.7: a diamino compound containing a monochloroisotriazine structure and starch are added to DMSO in a molar ratio of 0.8:1, wherein the starch is calculated as a polysaccharide unit, and the mixture is stirred and mixed evenly, and reacted at 110°C for 8 hours; after the reaction is completed, the mixture is precipitated in deionized water, filtered, washed with anhydrous methanol, dried, and crushed to obtain the above-mentioned 1#, 2# and 3# tertiary amine nitrogen-containing starch derivatives.

[0044] Example 1

[0045] 2.5g of 1# tertiary amine type nitrogen-containing starch derivative with a substitution degree of 0.6 and 0.35g of polyvinyl alcohol (PVA67000) with a molecular weight of 67000Da were mixed and dissolved in 15ml of water, and the pH was adjusted to 2 with hydrochloric acid. 5ml of soybean oil was added and the mixture was quickly emulsified with an emulsifier. 0.5g of a crosslinking agent was added to the emulsion, wherein R5 to R 10 All of them are -CH2OCH3, stirred until gel is formed, sealed and reacted at 40℃ for 12h. Then the water is dried and the oil droplets are washed away with ethyl acetate to obtain a porous anion exchange resin based on 1# tertiary amine type nitrogen-containing starch. The resin does not swell in pure water, and the swelling rate in HCl solution with pH=2.5 for 24 hours is 15%.

[0046] Figure 1 a is a schematic diagram of the preparation process of Example 1, and 1b is a reaction equation. Figure 2 It is the structural characterization of the product, where 2a is the infrared spectrum and 2b is 13 C solid NMR spectrum, 2c is the thermogravimetric curve of the product. In the infrared spectrum, the product has -1 The peak at 1020-1160cm -1 The COC stretching vibration peak at is significantly enhanced, indicating the formation of new cross-linked ether bonds. 13 In the C NMR spectrum, the C6 peak on the starch polysaccharide unit appeared at 58-65 ppm, and in the product this peak was obviously shifted to the low field, which indicated that the -OH on the starch C6 formed an ether bond and a cross-linked structure, proving that the target product was obtained.

[0047] Comparative Example 1

[0048] The only difference between this comparative example and Example 1 is that PVA67000 is not used to construct the second network during the cross-linking process, and an ion exchange resin of a single cross-linked starch network is obtained.

[0049] The preparation method is the same as that of Example 1. It is found that the resin prepared in Comparative Example 1 does not swell in pure water, and its 24-hour swelling rate in a HCl aqueous solution with a pH of 2.5 is 550%, indicating that the double network resin is more tightly cross-linked than the single network resin and has better water resistance.

[0050] Comparative Example 2

[0051] The only difference between this comparative example and Example 1 is that no emulsion is used as a porogenic template, that is, no oil phase is added to prepare the oil-in-water emulsion, and the preparation method is the same as Example 1, thereby obtaining a non-porogenic tertiary amine starch-based ion exchange resin.

[0052] Figure 3 3a and 3b are scanning electron micrographs of the starch-based ion exchange resins obtained in Comparative Example 2 and Example 1, respectively. The product of Comparative Example 2 is a solid block particle, while the product obtained in Example 1 has dense pores and is Figure 3 It can be seen from ce that the pore size of the porous structure is about 1 μm, so the specific surface area of ​​the resin is increased by pore creation.

[0053] Embodiments 2 to 9

[0054] The method is the same as in Example 1, that is, the tertiary amine type nitrogen-containing polysaccharide derivative [A(B) i ] n The polysaccharide unit residue A in the resin is replaced with one of the polysaccharide unit residues of cellulose, hemicellulose, chitin, guar gum, chitosan, xylan, glucomannan, and cyclodextrin to obtain anion exchange resins based on different biomass polysaccharides.

[0055] Example 10

[0056] 2.5g of 2# tertiary amine type nitrogen-containing starch derivative with a substitution degree of 0.6 and 0.35g of PVA67000 were mixed and dissolved in 15ml of water, and the pH was adjusted to 2 with hydrochloric acid. 5ml of soybean oil was added and the mixture was quickly emulsified with an emulsifier. 0.5g of a crosslinking agent was added to the emulsion, wherein R5 to R 10 All of them are -CH2OCH3, stirred until gel is formed, sealed and reacted at 40°C for 12 hours. Then the water is dried and the oil droplets are washed with ethyl acetate to obtain a porous highly hydrophobic anion exchange resin based on 2# tertiary amine type nitrogen-containing starch derivative.

[0057] Examples 11 to 18

[0058] The method is the same as that of Example 10, that is, the starch polysaccharide unit residues in the 2# tertiary amine type nitrogen-containing starch derivative are replaced with one of the polysaccharide unit residues of cellulose, hemicellulose, chitin, guar gum, chitosan, xylan, glucomannan, and cyclodextrin to obtain highly hydrophobic anion exchange resins based on different biomass polysaccharides.

[0059] Embodiment 19

[0060] Dissolve 2.5g of tertiary amine type 3# nitrogen-containing starch derivative with a substitution degree of 0.6 and 0.35g of PVA67000 in 15ml of water, adjust pH to 1.5 with hydrochloric acid, add 5ml of soybean oil and emulsify quickly with an emulsifier. Add 0.5g of a crosslinking agent to the emulsion, wherein R5 to R 10 All of them are -CH2OCH3. Stir until gel is formed, seal and react at 40°C for 12 hours. Then dry the water and wash the oil droplets with ethyl acetate to obtain a porous zwitterionic ion exchange resin based on 3# tertiary amine type nitrogen-containing starch.

[0061] Examples 20-27

[0062] The method is the same as that of Example 19, that is, the starch polysaccharide unit residues in the 3# tertiary amine type nitrogen-containing starch derivative are replaced with one of the polysaccharide unit residues of cellulose, hemicellulose, chitin, guar gum, chitosan, xylan, glucomannan, and cyclodextrin to obtain amphoteric ion exchange resins based on different biomass polysaccharides.

[0063] Embodiments 28 to 30

[0064] The method is the same as that of Example 1, except that the 1# tertiary amine type nitrogen-containing starch derivative with a substitution degree of 0.6 is replaced by 1# tertiary amine type nitrogen-containing starch derivatives with substitution degrees of 0.2, 0.4, and 0.8, respectively, to obtain tertiary amine type starch-based anion exchange resins with different total exchange capacities. The elastic modulus G' of the cross-linked wet product is measured using an advanced rheometer, as shown in FIG. Figure 4 As shown in Figure a, the elastic modulus of the wet product gradually decreases with the increase of the degree of substitution, which indicates that the increase of the substituent group B will lead to an increase in the reaction steric hindrance of -OH on the polysaccharide, which is not conducive to the cross-linking process.

[0065] Examples 31 to 34

[0066] Using PVA with different molecular weights, namely PVA30000, PVA10000, PVA5000, PVA1000, instead of PVA67000 in Example 1, cross-linked products with different strengths were obtained, and the elastic modulus G' of the cross-linked wet product was characterized by an advanced rheometer, as shown in FIG. Figure 4 As shown in Figure b, the larger the molecular weight of PVA, the higher the G' of the wet product, indicating that there are physical interactions such as chain entanglement and interpenetration between PVA and the polysaccharide chain. Therefore, the cross-linking strength can be regulated by adjusting the molecular weight of PVA.

[0067] Embodiments 35 to 39

[0068] The method is the same as that of Example 1, except that the amount of PVA67000 added is changed, that is, 3.0wt%, 6.7wt%, 11.2wt%, 14.7wt%, and 19.1wt% of PVA67000 are added to the total mass of the reactants, respectively. The obtained wet products have different elastic moduli G', such as Figure 4 c. This shows that the amount of PVA added has a significant effect on the strength of the product.

[0069] Embodiments 40 to 45

[0070] Ethylenediamine, diethylenetriamine, polyethylene glycol, polyacrylic acid, carboxymethyl starch and hydroxyethyl cellulose were used to replace PVA67000 in Example 1 to obtain double-network starch-based anion exchange resin with different second networks.

[0071] Embodiment 46

[0072] Mix and dissolve 2.5g of 1# tertiary amine type nitrogen-containing starch derivative with a substitution degree of 0.6 and 0.35g of oxalic acid in 15ml of water. Oxalic acid is used as an acidic agent and a second network to reduce the use of hydrochloric acid. Then add 5ml of soybean oil and emulsify quickly with an emulsifier. Add 0.5g of a crosslinking agent to the emulsion, wherein R5 to R 10 All of them are -CH2OCH3, stirred until gel is formed, sealed and reacted at 40°C for 12 hours. Then the water is dried and the oil droplets are washed away with ethyl acetate to obtain a porous anion exchange resin based on 1# tertiary amine type nitrogen-containing starch derivative.

[0073] Embodiments 47-48

[0074] The method is the same as that of Example 46, except that oxalic acid is replaced by malonic acid and citric acid, thereby obtaining an anion exchange resin based on 1# tertiary amine type nitrogen-containing starch derivative and containing an ester group.

[0075] Embodiments 49 to 50

[0076] The method is the same as Example 46, except that the volume ratio of oil to water constituting the emulsion is changed from 1:3 to 1:2 and 1:4, respectively, to obtain porous starch-based ion exchange resins with different pore morphologies and porosities. Figure 5 These are scanning electron microscope images of products obtained with different oil:water volume ratios. It can be seen that the products all have dense porous structures.

[0077] Embodiment 51

[0078] 2.5g of 1# tertiary amine type nitrogen-containing starch derivative with a substitution degree of 0.6 and 0.35g of PVA67000 were mixed and dissolved in 15ml of water, and the pH was adjusted to 2 with hydrochloric acid. 5ml of cyclohexane was added and the mixture was quickly emulsified with an emulsifier. 0.5g of a crosslinking agent was added to the emulsion, wherein R5 to R 10 All of them are -CH2OCH3, stirred until gel is formed, sealed and reacted at 40°C for 12 hours. Then the water is dried and the cyclohexane is washed away with ethanol to obtain a porous anion exchange resin based on 1# tertiary amine type nitrogen-containing starch derivative.

[0079] Embodiment 52-53

[0080] The method is the same as Example 51, except that cyclohexane is replaced by n-hexane and ethyl acetate is used as the oil phase of the emulsion template, and a porous starch-based ion exchange resin is also obtained.

[0081] Embodiments 54 to 58

[0082] The method is the same as that of Example 51, except that the amount of crosslinking agent added is changed to 9wt%, 19wt%, 25wt%, 30wt% and 40wt% of the total mass fraction of the reactants. Starch-based ion exchange resins with different crosslinking degrees are obtained. The elastic modulus G' of the wet product is as follows: Figure 4 As shown in Figure d, when the amount of the crosslinking agent is 25wt%, it has the highest crosslinking degree and elastic modulus.

[0083] Embodiments 59 to 60

[0084] The method is the same as that of Example 51, except that the cross-linking agent (R5 to R 10 are -CH2OCH3) are replaced with cross-linking agents with high imino content (R5 to R 10 At least 1 to 3 of them are -H, and the rest are -CH2OCH3) and a crosslinking agent with a high hydroxymethyl content (R5 to R5 of Formula I-2 10 At least 1 to 3 of them are -CH2OH and the rest are -CH2OCH3), thereby obtaining tertiary amine starch-based anion exchange resins with different degrees of cross-linking.

[0085] Test Example 1

[0086] First, prepare 100 ml of a 2 g / L reactive brilliant blue X-BR dye solution in a conical flask and adjust the pH to 2.0. Weigh 0.1 g of the starch-based ion exchanger obtained in Example 1 and add it to a conical flask, and oscillate it in a constant temperature oscillator at 25°C for sufficient adsorption. After 2 hours, take the supernatant and measure the remaining dye concentration on UV-vis and calculate the adsorption capacity. The results show that the maximum adsorption capacity of the ion exchanger is 1560 mg / g. Under the same conditions, the adsorption capacity of the non-porous starch-based ion exchanger obtained in Comparative Example 3 is only 200 mg / g.

[0087] The adsorbed exchanger was collected by filtration and desorbed with a Na2CO3 solution containing 20% ​​to 50% ethanol. The desorption rate increased from 67% to 95% as the ethanol concentration increased. The desorbed ion exchanger was subjected to ten cycles of adsorption and desorption, and the adsorption capacity of the exchanger after ten cycles was 1390 mg / g.

[0088] The remaining embodiments of the present invention have the same effects as embodiment 1.

[0089] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. An anion exchange resin based on a tertiary amine-containing nitrogen polysaccharide derivative, characterized in that the structural general formula of the anion exchange resin is shown in Formula I: [A(B) i ] n -(CL) j -D(Ⅰ) In Formula I, [A(B) i ] n It is a tertiary amine type nitrogen-containing polysaccharide derivative, wherein A is a polysaccharide unit residue, B is a substituent on the polysaccharide unit residue, and the degree of substitution is i; D is a compound having multiple hydroxyl groups, carboxyl groups or primary amine groups; (CL) j is a cross-linking agent with a functionality of j, which can undergo cross-linking reaction with both A and D; the anion exchange resin is an insoluble porous double-network tertiary amine polysaccharide derivative formed by crosslinking a tertiary amine-containing nitrogen polysaccharide derivative and a compound having polyhydroxy, carboxyl or primary amine groups simultaneously.

2. The anion exchange resin based on tertiary amine nitrogen-containing polysaccharide derivative according to claim 1, characterized in that: The pore size of the anion exchange resin based on the tertiary amine-containing nitrogen polysaccharide derivative is 0.1 μm to 1.0 μm, and the porosity is 17% to 67%.

3. The anion exchange resin based on tertiary amine nitrogen-containing polysaccharide derivative according to claim 1, characterized in that: In Formula I, the glycan unit residue A includes one or more of starch, cellulose, hemicellulose, chitin, guar gum, chitosan, xylan, glucomannan, cyclodextrin or polysaccharide unit residues prepared by acidolysis, oxidation, crosslinking.

4. The anion exchange resin based on tertiary amine nitrogen-containing polysaccharide derivative according to claim 1, characterized in that: In Formula I, the substituent B on the glycan unit residue has a diamino group with a triazine ring as a bridge group, which can randomly replace the H on -OH or -NH2 at any position on the polysaccharide unit, and the degree of substitution is 0 < i ≤ 3, and it has the structural general formula shown in Formula I-1: In Formula I-1, R1, R2, R3, and R4 are each independently selected from -H, C1 to C 11 Alkyl, C1~C 11 Aryl, C1-C8 carboxylic acid, C1-C8 alcohol, C1-C8 thiol or C1-C8 alkoxymethyl.

5. The anion exchange resin based on tertiary amine nitrogen-containing polysaccharide derivative according to claim 1, characterized in that: In Formula I, the compound D having polyhydroxy, carboxyl or primary amine groups is selected from one or more of C1-C8 polyols, C1-C8 polycarboxylic acids, C1-C8 polyamines and polymers containing hydroxyl, carboxyl and primary amine groups; the polymers containing hydroxyl, carboxyl and primary amine groups include one or more of polyethylenepolyamine, polyvinyl alcohol, polyethylene glycol, polyacrylic acid, carboxymethyl starch and hydroxyethyl cellulose; the total number of hydroxyl, carboxyl and primary amine groups on the molecular chain of the compound D having polyhydroxy, carboxyl or primary amine groups ≥ 2.

6. The anion exchange resin based on tertiary amine nitrogen-containing polysaccharide derivative according to claim 5, characterized in that: In Formula I, the tertiary amine type nitrogen-containing polysaccharide derivative [A(B) i ] n The mass ratio of the compound D having multiple hydroxyl groups, carboxyl groups or primary amine groups is 1:0.02 to 1:0.

2.

7. The anion exchange resin based on tertiary amine nitrogen-containing polysaccharide derivative according to claim 1, characterized in that: In Formula I, the crosslinking agent (CL) j It is a compound containing j alkoxymethyl groups with melamine as the bridge group, and the alkoxy groups on it can be randomly replaced by -OH or amine groups containing active hydrogen on A and D, and has the general structural formula shown in Formula I-2: In Formula I-2, R5 to R 10 are independently selected from -H, -CH2OH, -CH2OCH3, -CH2OCH2CH3, -CH2O(CH2)2CH3 or -CH2O(CH2)3CH3, and R5 to R 10 The total number of -H and -CH2OH is <5.

8. The anion exchange resin based on tertiary amine nitrogen-containing polysaccharide derivative according to claim 7, characterized in that: In Formula I, the tertiary amine type nitrogen-containing polysaccharide derivative [A(B) i ] n With crosslinker (CL) j The mass ratio is 1:0.05~1:0.

4.

9. A method for preparing an anion exchange resin based on a tertiary amine nitrogen-containing polysaccharide derivative according to any one of claims 1 to 8, characterized in that: comprising the following steps: The tertiary amine type nitrogen-containing polysaccharide derivative [A(B) i ] n After adding a compound D having multiple hydroxyl groups, carboxyl groups or primary amine groups into water, adjusting the pH of the solution to 2 to 6 to dissolve it, then adding an oil phase for high-speed emulsification to obtain an emulsion template; Adding a crosslinker (CL) to the latex template j After mixing, the mixture is reacted in a closed environment at 20° C. to 60° C. for 0 h to 24 h, and then dried and the oil droplets are washed off to obtain the anion exchange resin based on the tertiary amine nitrogen-containing polysaccharide derivative.

10. The preparation method according to claim 9, characterized in that: The tertiary amine type nitrogen-containing polysaccharide derivative [A(B) i ] n The mass ratio of water is 1:1 to 1:20; the oil phase includes one or more of vegetable oil, gasoline, paraffin oil, n-hexane, cyclohexane, toluene, ethyl acetate; the volume ratio of the oil phase to water is 1:0.5 to 1:5.

Citation Information

Patent Citations

  • Hydrophilic / hydrophobic controllable conversion tertiary amine type nitrogenous glycan derivative, and preparation method and application thereof

    CN110551226A

  • Alkali anion exchange resin

    CN1166381A

  • Nitrogenous polysaccharid derivative and its preparing process

    CN1962700A